2013
DOI: 10.1039/c3em30816b
|View full text |Cite
|
Sign up to set email alerts
|

Application of fluorescence and PARAFAC to assess vertical distribution of subsurface hydrocarbons and dispersant during the Deepwater Horizon oil spill

Abstract: We evaluated the use of excitation and emission matrix (EEM) fluorescence and parallel factorial analysis (PARAFAC) modeling techniques for monitoring crude oil components in the water column. Four of the seven derived PARAFAC loadings were associated with the Macondo crude oil components. The other three components were associated with the dispersant, an unresolved component and colored dissolved organic matter (CDOM). The fluorescence of the associated benzene and naphthalene-like components of crude oil exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 38 publications
9
31
0
Order By: Relevance
“…Based on the good experience from the DWH spill, Caruso et al (2013) suggested that SAR should be used more in direct spill response activities and to optimize available response resources. Several studies have used fluorescence excitation-emission matrix spectra and parallel factor analysis techniques (EEM-PARAFAC) for detecting oil degradation products in deep-water or surface-water samples from NGOM (Bianchi et al, 2014;Mendoza et al, 2013;Zhou et al, 2013a;Zhou et al, 2013b). The technique can detect oil derivatives which are transformed into the dissolved organic matter (DOM) pool, no longer recognizable as oil or oil derivatives by traditional HC analyses.…”
Section: Characterization and Behaviour Of Released Oil And Gasmentioning
confidence: 99%
“…Based on the good experience from the DWH spill, Caruso et al (2013) suggested that SAR should be used more in direct spill response activities and to optimize available response resources. Several studies have used fluorescence excitation-emission matrix spectra and parallel factor analysis techniques (EEM-PARAFAC) for detecting oil degradation products in deep-water or surface-water samples from NGOM (Bianchi et al, 2014;Mendoza et al, 2013;Zhou et al, 2013a;Zhou et al, 2013b). The technique can detect oil derivatives which are transformed into the dissolved organic matter (DOM) pool, no longer recognizable as oil or oil derivatives by traditional HC analyses.…”
Section: Characterization and Behaviour Of Released Oil And Gasmentioning
confidence: 99%
“…Our investigations focused on crude oil samples collected from oil spill sites and crude seawater from the Narragansett Bay, with 10 mM of various cyclodextrins dissolved in the seawater. The chemical profile of oil spill oil collected directly from a Gulf of Mexico site has been well characterized in a number of references [26,27] and been shown to contain a diverse mixture of organic compounds including polycyclic aromatic hydrocarbons and a variety of more polar oxygenated metabolites [28]. Tar ball components have been similarly well-characterized using a variety of spectroscopic techniques [29][30][31].…”
Section: Fig 2 Illustration Of Energy Transfer Efficiency For a Genermentioning
confidence: 99%
“…PAHs are photochemically reactive and have peculiar fluorescence properties, that make them part of both chromophoric DOM (CDOM) and fluorescent DOM (FDOM) (Christensen et al, 2005;Ferretto et al, 2014;Mendoza et al, 2013. CDOM is defined as the fraction of DOM capable of absorbing light at the visible and UV wavelengths, while FDOM is the fraction of CDOM capable of fluorescence.…”
Section: Introductionmentioning
confidence: 99%